Exploitation of mesopelagic fish stocks can impair the biological pump and food web dynamics in the ocean - Dişa, Deniz; Akoglu, Ekin; Salihoglu, Baris (Frontiers in Marine Science, 2024)
The demand for marine living resources is increasing at an unprecedented scale because of the need for continuous food provision to the world’s population. The potential of already exploited fish stocks to meet this demand is limited. Therefore, mesopelagic fish have recently become attractive potential targets for fisheries because of their vast conjectured biomass. However, the role of mesopelagic fish in marine ecosystems is poorly understood. Before developing commercial exploitation plans, the relationship between mesopelagic fish and other groups in the marine food web and biogeochemical cycles should be analyzed quantitatively. In this study, we coupled a one-dimensional biogeochemical model (North Atlantic Generic Ecosystem Model) with a higher-trophic-level food web model (Ecopath with Ecosim) for the Sargasso Sea in the North Atlantic to investigate changes in carbon export and trophodynamics under two mesopelagic fish harvesting scenarios. The coupled model represented the marine food web from plankton to fish and mammals, vertical carbon export dynamics, and their interaction with fisheries. The results showed that when mesopelagic fish were not harvested, they contributed approximately 6% of the total carbon export in the surface waters, but up to 40% of the total carbon export below 400 m. Harvesting mesopelagic fish altered the energy transfers within the food web as well as to fisheries. The ecological footprint of fisheries increased significantly. Due to declining competition in the food web, epipelagic fish increased to exert elevated grazing pressure on phytoplankton; hence, phytoplankton-mediated carbon export decreased. The total carbon export decreased by 14% due to the decreases in mesopelagic fish- and phytoplankton-mediated carbon exports. The simulated increase in zooplankton- and non-mesopelagic fish-mediated carbon exports (up to 92% and 96%, respectively) did not compensate for the total decrease in carbon exports under harvesting scenarios. The findings of this study highlighted that mesopelagic fish not only have a direct control on carbon dynamics by their metabolic releases and diel vertical migration, but also strong indirect controls through prey-predator interactions within the food web. Therefore, the implications of harvesting mesopelagic fish should be carefully considered from a holistic perspective.